A total closed chest sheep model of cardiogenic shock by percutaneous intracoronary ethanol injection - Mario Rienzo (Nature Portfolio, 2020)
Abstract To develop a reproducible and stable closed chest model of ischemic cardiogenic shock in sheep, with high survival rate and potential insight into human pathology. We established a protocol for multi-step myocardial alcoholisation of the left anterior descending coronary artery by percutaneous ethanol injection. A thorough hemodynamic assessment was obtained by invasive and non-invasive monitoring devices. Repeated blood samples were obtained to determine haemoglobin and alcohol concentration, electrolytes, blood gas parameters and cardiac troponin I. After sacrifice, tissue was excised for quantification of infarction and histology. Cardiogenic shock was characterized by a significant decrease in mean arterial pressure (− 33%), cardiac output (− 29%), dP/dt max (− 28%), carotid blood flow (− 22%), left ventricular fractional shortening (− 28%), and left ventricle end-systolic pressure–volume relationship (− 51%). Lactate and cardiac troponin I levels increased from 1.4 ± 0.2 to 4.9 ± 0.7 mmol/L (p = 0.001) and from 0.05 ± 0.02 to 14.74 ± 2.59 µg/L (p = 0.001), respectively. All haemodynamic changes were stable over a three-hour period with a 71% survival rate. The necrotic volume (n = 5) represented 24.0 ± 1.9% of total ventricular mass. No sham exhibited any variation under general anaesthesia. We described and characterized, for the first time, a stable, reproducible sheep model of cardiogenic shock obtained by percutaneous intracoronary ethanol administration.